2010
DOI: 10.1111/j.1365-2710.2009.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards concordance in healthcare: perspectives of general practitioners, complementary and alternative medicine practitioners and pharmacists in Australia

Abstract: Partnerships and concordance are desirable concepts for optimal healthcare. The concept of concordance is based on negotiation between equals in a therapeutic relationship, forming a therapeutic alliance between all partners. One field of healthcare in which concordant relationships may be particularly desirable is complementary and alternative medicine (CAM). CAM is increasingly used by consumers worldwide, and provider-patient relationships are important across the spectrum of CAM-to-conventional medicine; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 42 publications
1
24
0
1
Order By: Relevance
“…This is consistent with another trend - the increasing focus on 'concordance' in relationships between healthcare practitioners and consumers in the conventional healthcare model [10]. Concordance is based on negotiation between partners in a therapeutic relationship (consumer and healthcare practitioners), its strength being respect for the consumer's agenda and the creation of openness in the relationship [11-14].…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…This is consistent with another trend - the increasing focus on 'concordance' in relationships between healthcare practitioners and consumers in the conventional healthcare model [10]. Concordance is based on negotiation between partners in a therapeutic relationship (consumer and healthcare practitioners), its strength being respect for the consumer's agenda and the creation of openness in the relationship [11-14].…”
Section: Introductionsupporting
confidence: 74%
“…The concept of problem identification arising from differing perceptions of the same issue/statement is very useful for future intervention design and evaluation. The principle behind this PDS was to investigate similarities and differences between consumers' ratings of issues relating to CAM and concordance compared to those rated by healthcare practitioners in a previous study, reported elsewhere [10]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been observed in the last decades a constant increase of the use of herbal medicines, which has been encouraging scientific studies for the discovery of new substances with therapeutic action and for the confirmation of the efficacy and safety of medicines derived from plants (Hansen et al, 2010;Ma et al, 2010;Moraes et al, 2012). The safe use of herbal drugs requires knowledge of their chemical properties and possible adverse effects (Fejzic et al, 2010;Teschke et al, 2010). Plant materials are used throughout the world as home remedies or raw materials for the pharmaceutical industry and represent a substantial proportion of the global drug market (Bosnic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%